DAMPAK IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER SISWA - Nurmalasari, Siti; Abidin, Jaenal; Ferianto (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2024)
This study examines the impact of implementing Islamic Religious Education (PAI) on students' character development. Islamic Religious Education plays an important role in shaping the morals and ethics of individuals within the Muslim community. The objective of this research is to identify the effects of applying Islamic religious education on children's character formation. The focus of the study is to gain a deeper understanding of how Islamic religious education influences children's character development. The research methodology uses a Systematic Literature Review (SLR) to identify, evaluate, and interpret findings related to the research topic. The research results show that PAI education has a significant impact on students' character formation, as reflected in a strong understanding of morals and the application of Islamic values in daily life. Additionally, PAI education contributes to increased religious knowledge and the development of practical skills among students. Thus, PAI education not only provides a theoretical understanding of Islam but also shapes students into responsible and virtuous individuals. Although there are other external factors that influence moral development, PAI education remains a fundamental foundation in character education in schools.